Pharmacogenomics and Personalized Medicine in Type 2 Diabetes Mellitus: Potential Implications for Clinical Practice - Venkatachalapathy P (Dove Medical Press, 2021)
Poongothai Venkatachalapathy,1 Sruthi Padhilahouse,1 Mohan Sellappan,1 Tharunika Subramanian,2 Shilia Jacob Kurian,3 Sonal Sekhar Miraj,3 Mahadev Rao,3 Ashwin Ashok Raut,4 Rupinder Kaur Kanwar,4 Jitendra Singh,4 Sagar Khadanga,5 Sukumar Mondithoka,5 Murali Munisamy4 1Department of Pharmacy Practice, Karpagam College of Pharmacy, Coimbatore, Tamilnadu, India; 2Karpagam Faculty of Medical Sciences and Research, Coimbatore, India; 3Department of Pharmacy Practice, Manipal College of Pharmaceutical Sciences, Manipal Academy of Higher Education, Manipal, Karnataka, India; 4Translational Medicine Centre, All India Institute of Medical Sciences, Bhopal, Madhya Pradesh, India; 5Department of General Medicine, All India Institute of Medical Sciences, Bhopal, Madhya Pradesh, IndiaCorrespondence: Murali MunisamyTranslational Medicine Centre, All India Institute of Medical Sciences, Bhopal, 462020, Madhya Pradesh, India, Tel +91-9600-883-284Email murali.tmc@aiimsbhopal.edu.inAbstract: Type 2 diabetes mellitus (T2DM) is the most common form of diabetes, and is rising in incidence with widespread prevalence. Multiple gene variants are associated with glucose homeostasis, complex T2DM pathogenesis, and its complications. Exploring more effective therapeutic strategies for patients with diabetes is crucial. Pharmacogenomics has made precision medicine possible by allowing for individualized drug therapy based on a patient’s genetic and genomic information. T2DM is treated with various classes of oral hypoglycemic agents, such as biguanides, sulfonylureas, thiazolidinediones, meglitinides, DPP4 inhibitors, SGLT2 inhibitors, α-glucosidase inhibitors, and GLP1 analogues, which exhibit various pharmacogenetic variants. Although genomic interventions in monogenic diabetes have been implemented in clinical practice, they are still in the early stages for complex polygenic disorders, such as T2DM. Precision DM medicine has the potential to be effective in personalized therapy for those suffering from various forms of DM, such as T2DM. With recent developments in genetic techniques, the application of candidate-gene studies, large-scale genotyping investigations, genome-wide association studies, and “multiomics” studies has begun to produce results that may lead to changes in clinical practice. Enhanced knowledge of the genetic architecture of T2DM presents a bigger translational potential. This review summarizes the genetics and pathophysiology of T2DM, candidate-gene approaches, genome-wide association studies, personalized medicine, clinical relevance of pharmacogenetic variants associated with oral hypoglycemic agents, and paths toward personalized diabetology.Keywords: pharmacogenomics, personalized medicine, type 2 diabetes, antidiabetic drugs